ALZHEIMER’S DISEASE IN THE FAMILY (Annual of the Faculty of Philosophy in Skopje, 2024)
Alzheimer’s, accounting for 60-80% of dementia cases, presents a specific pathologyand a range of symptoms, including memory loss, impaired reasoning, andother cognitive declines. The disease’s progression and management require a comprehensiveapproach involving professional care, family involvement, and individualizedcare plans.The research focuses on methods for working with individuals with Alzheimer’sdisease and their families, highlighting the importance of communication in implementingindividualized care plans. It aims to show that a well-prepared care plan, coupledwith effective communication with family members, can improve quality of life andpotentially slow disease progression. It was conducted in two parts: a questionnaire forcaregivers working with Alzheimer’s patients and a semi-structured interview with 33family members of individuals diagnosed with the disease. This approach provided bothquantitative and qualitative data, offering a comprehensive understanding of the issues.To improve Alzheimer’s care, we recommend enhancing family involvementthrough structured models and training, increasing the accessibility of specializedservices, promoting professional development, strengthening ethical communicationstandards, implementing comprehensive support systems, and regularly evaluatingcare plans. These measures aim to provide holistic and effective care strategies, improvingthe quality of life for individuals with Alzheimer’s and their families.
Keywords: Alzheimer’s disease; Dementia care; Individualized care plans; Family involvement; Professional training